Building structure works estimation program – BEST’s - Mohd Sarman, Asmawan; Mazlan, Elis Mardzianah (2008)
Building Structure Works Estimation Program – BEST’s has been developed for the use of cost estimation on building structure works such as piling works, excavation works, foundation works, frames works and extension works. The objectives for this project are to develop a building work estimating program, to increase the accuracy of estimation and to store and retrieve the estimation. Methodology for this project development is using the SDLC Waterfall (System Development Life Cycle, also as "System Design Life Cycle") which consists of six stages such as project planning, requirements definition, design, development, integration & test and installation & acceptance. This program was developed based on window application. The system design will describe how the system is implemented and defined. For this estimation program, Use Case Diagram (USD) and Data Flow Diagram (DFD) are used to show the workflow of the object oriented approach. The database system was developed based on the standard schedules of rates from Jabatan Kerja Raya (JKR) year 2007, Malaysia. The user friendly interface and helpful button of the estimation program allow the user to surf the system in a better way. This estimation program is completed with the calculation function, printout function, search and edit of histories estimation function. Users are allowed to store and retrieve estimation data and information. This estimation program hopefully can be useful to help those individual, contractors and company in their project in such that this system will shorten the time usage to do the estimation compare with the old practice. Besides, increase the accuracy of estimation, the usage of this system would enable those contractors can extend their business and compete with other company in building works sector.